Genetic architecture, biochemical underpinnings and ecological impact of floral UV patterning. Issue 5 (23rd February 2016) - Brock, Marcus T.; Lucas, Lauren K.; Anderson, Nickolas A.; Rubin, Matthew J.; Cody Markelz, R. J.; Covington, Michael F.; Devisetty, Upendra K.; Chapple, Clint; Maloof, Julin N.; Weinig, Cynthia
Abstract: Floral attraction traits can significantly affect pollinator visitation patterns, but adaptive evolution of these traits may be constrained by correlations with other traits. In some cases, molecular pathways contributing to floral attraction are well characterized, offering the opportunity to explore loci potentially underlying variation among individuals. Here, we quantify the range of variation in floral UV patterning (i.e. UV 'bulls‐eye nectar guides) among crop and wild accessions of Brassica rapa . We then use experimental crosses to examine the genetic architecture, candidate loci and biochemical underpinnings of this patterning as well as phenotypic manipulations to test the ecological impact. We find qualitative variation in UV patterning between wild (commonly lacking UV patterns) and crop (commonly exhibiting UV patterns) accessions. Similar to the majority of crops, recombinant inbred lines (RILs) derived from an oilseed crop × WI fast‐plant ® cross exhibit UV patterns, the size of which varies extensively among genotypes. In RILs, we further observe strong statistical‐genetic and QTL correlations within petal morphological traits and within measurements of petal UV patterning; however, correlations between morphology and UV patterning are weak or nonsignificant, suggesting that UV patterning is regulated and may evolve independently of overall petal size. HPLC analyses reveal a high concentration of sinapoyl glucose in UV‐absorbing petal regions, which, in concert with physical locations of UV‐trait QTLs, suggest a regulatory and structural gene as candidates underlying observed quantitative variation. Finally, insects prefer flowers with UV bulls‐eye patterns over those that lack patterns, validating the importance of UV patterning in pollen‐limited populations of B. rapa .